Affordable Housing as an Alternative for Reconstruction After an Earthquake in Rural Areas: Al Haouz, Morocco - Benlarbi, Wiam; Karaman, Aykut (International Journal for Disaster and Development Interface, 2025)
Post-earthquake rebuilding planning is essential for the long-term development of earthquake-affected areas. Approaches to community resilience in rural settings focus on how communities adjust to changes and shocks. This study utilizes a resident resilience method to analyze affordable housing during earthquake rebuilding in Morocco in comparison to other countries that took this alternative as a solution. Methods used included semi-structured interviews, participant observation, Geographic mapping, and secondary data analysis. This study describes how resources were mobilized following the tragedy to solve short- and long-term housing options through prefabricated and cheap homes, while considering the area's unique building materials and space management.